Breathable 3D Supercapacitors Based on Activated Carbon Fiber Veil. Issue 11 (21st August 2018) - Shin, Dongwoo; Shen, Caiwei; Sanghadasa, Mohan; Lin, Liwei
Abstract: For supercapacitors to become truly wearable to power various portable electronics, they must not only possess high power and energy density with long cycle life, but also provide comfort and durability. Here, a facile method of fabricating substrate‐free and freestanding breathable 3D supercapacitors using veil‐based electrodes with activated carbon fibers (ACFs) is reported. The conductive and high porous electrodes are lightweight, breathable, flexible, foldable, and tailorable with achieved high energy density of 5.52 Wh kg −1 and >86.6% capacitance retention over 10 000 charge–recharge cycles under various mechanical deformations such has folding, cutting, and compression. Different from the existing energy storage systems, the mechanically reliable supercapacitors can be integrated into parts of garments that are susceptible to a combination of anomalous mechanical deformations such as the inner elbow for 3D wearable energy storage applications. Abstract : Breathable 3D supercapacitors based on activated carbon fiber veil are integrated into parts of garments that are susceptible to a combination of anomalous mechanical deformations for 3D wearable energy storage applications.